A Beautiful mind - Howard, Ron.; DreamWorks Production (Film). ([s.l.] DreamWorks Pictures, 2001)
A brilliant mathematician John Nash, on the brink of international acclaim when he become entangled in mysterious conspiracy. Now only his devoted wife can help him in this powerful story of courage, passion and triumph.
DVD
Written by Akira Goldsman, produced by Brian Grazer, directed by Ron Howard
Jennifer Connelly, Paul Bettary, Adam Goldberg
Keywords: Feature films